Detection ratios on winter surveys of Rocky Mountain Trumpeter Swans Cygnus buccinator - Bart, Jonathan; Mitchell, Carl D; Fisher, Michael N; Dubovsky, James A (Wildfowl, 2013)
We estimated the detection ratio for Rocky Mountain Trumpeter Swans Cygnus buccinator that were counted during aerial surveys made in winter. The standard survey involved counting white or grey birds on snow and ice and thus might be expected to have had low detection ratios. On the other hand, observers were permitted to circle areas where the birds were concentrated multiple times to obtain accurate counts. Actual numbers present were estimated by conducting additional intensive aerial counts either immediately before or immediately after the standard count. Surveyors continued the intensive surveys at each area until consecutive counts were identical. The surveys were made at 10 locations in 2006 and at 19 locations in 2007. A total of 2,452 swans were counted on the intensive surveys. Detection ratios did not vary detectably with year, observer, which survey was conducted first, age of the swans, or the number of swans present. The overall detection ratio was 0.93 (90% confidence interval 0.82–1.04), indicating that the counts were quite accurate. Results are used to depict changes in population size for Rocky Mountain Trumpeter Swans from 1974–2007.